Calculating maternal polygenic risk scores from prenatal screening by cell-free DNA data - Corey, Victoria; Chavez, Mauro; Qasim, Layla; Dincer, Tevfik U.; Henry, Angela; Bagayan, Salome; Treadup, Sasha; Mehan, Mike; de Feo, Eileen; Kim, Sung (Frontiers in Genetics, 2025)
Polygenic Risk Scores (PRS) have enabled quantification of genetic risk for many common and complex traits. Here we developed a novel method to estimate maternal PRS using low-coverage whole genome sequencing data from prenatal screening by cell-free DNA data intended to screen for fetal chromosomal aneuploidies. A prospective study was conducted where 455 consented patients that performed prenatal screening by cell-free DNA as part of their standard of care were randomly selected. Cell-free DNA and genomic DNA were isolated from the plasma and buffy coat of the blood drawn from pregnant women, respectively. Cell-free DNA was sequenced at ∼0.25x coverage while genomic DNA was sequenced at ∼15x coverage. The sequence data was used to impute genotypes which were then used to calculate PRS for paired comparisons. There was a high correlation (average = ∼0.9 across different PRS panels and panel sizes) between PRS from prenatal screening by cfDNA data and PRS from genome sequence data of the buffy coat. This proof-of-concept study illustrates that maternal PRS can be calculated using low-coverage prenatal screening by cfDNA sequence data with high accuracy.